Chinese SLE Treatment and Research Group Registry (CSTAR) XIV: the subjective well-being of patients with systemic lupus erythematosus - Shi, Yue; Bi, Dandan; Wang, Yanhong; Li, Ruofan; Wu, Lijun; Zhao, Cheng; Wu, Zhenbiao; Duan, Xinwang; Xu, Jian; Zhan, Feng; Yang, Min; Liu, Shengyun; et al. (Frontiers in Medicine, 2022)
Background: Systemic lupus erythematosus (SLE) can significantly influence patients’ quality of life and subjective well-being (SWB), but the relationships between clinical characteristics, SWB and related psychological factors have been little studied Objective: To measure SWB in SLE patients and examine how major clinical determinants, emotional variables and related positive factors affect SWB. Methods: Overall, 1100 SLE patients from the Chinese SLE Treatment and Research Group (CSTAR) and 198 age and gender-matched individuals from the general population without self-reported SLE were invited to complete questionnaires of SWB evaluated by the satisfaction with life scale (SWLS), emotional variables assessed by the patient health questionnaire-9 (PHQ-9) and general anxiety disorder-7 (GAD-7) and related positive factors assessed by the self-esteem scale (SES), general self-efficacy scale (GESE) and Connor-Davidson resilience scale (CD-RISC). The multivariate linear regression was used to examine the relationship between clinical manifestations and SWB. Results: Life satisfaction were significantly lower (p<0.001) in SLE patients than in the general population. Active skin involvement (OR=0.923, 95%CI=0.868-0.981, p<0.05) was negatively associated with life satisfaction scores and age at enrollment (OR=1.160, 95%CI=1.092-1.230, p<0.001) were positively associated with life satisfaction scores in the multivariate regression model. The cumulative organ damage was significantly associated with depression (OR = 1.085, 95% CI = 1.022-1.153, p < 0.01) and the loss of self-esteem (OR = 1.067, 95%CI=1.004-1.133, p < 0.05). Conclusion: SWB provides useful insight into the impact of SLE on psychological health and opportunities to improve quality of life and clinical care.